Drug resistance and population structure of M.tuberculosis isolates from prisons and communities in Ethiopia. Issue 1 (December 2016) - Ali, Solomon; Beckert, Patrick; Haileamlak, Abraham; Wieser, Andreas; Pritsch, Michael; Heinrich, Norbert; Löscher, Thomas; Hoelscher, Michael; Niemann, Stefan; Rachow, Andrea
Abstract Background The population structure and drug resistance pattern ofMycobacterium tuberculosis complex (MTBC) isolates in Ethiopian prisons and some communities is still unknown. Methods A comparative cross sectional study was conducted on 126 MTBC strains isolated from prisons and communities in southwestern, southern and eastern Ethiopia. Phenotypic drug susceptibility testing was performed with the MGIT960 system. Combined 24-lociMycobacterium interspersed repetitive unit-variable number tandem repeat and spacer oligonucleotide typing methods were used to study the MTBC population structure. The obtained data from prisons and communities were compared using statistical tests and regression analysis. Results A diverse population structure with 11 different lineages and sub-lineages was identified. The predominant strains were the recently described Ethiopia_H37Rv like (27.52%) and Ethiopia_3 (16.51%) with equal lineage distribution between prisons and communities. 28.57% of prison strains and 31.82% of community strains shared the identical genotype with at least one other strain. The multidrug-resistance (MDR) prevalence of the community was 2.27% whereas that of prisons was 9.52%. The highest mono resistance was seen against streptomycin (15.89%). Conclusion Tuberculosis in communities and prisons is caused by a variety of MTBC lineages with predominance of local Ethiopian lineages. The increasing prevalence of MDR MTBC strains is alarming. These findings suggest the need for new approaches for control of MDR tuberculosis in Ethiopia.